Sistem Pemilihan Motor Bekas Menggunakan Metode Analitycal Hierarchy Process (AHP) Studi Kasus di Showroom Abi Motor Karawang - Purba, Febriana Angelia; Ridwan, Muhammad; Sukanta, Sukanta (Patria Artha Technological Journal, 2021)
Two-wheeled motorcycles have recently been in great demand, apart from being affordable, these vehicles have more functions than two-wheeled vehicles in general. The role of fast motorbikes is to replace pedal bicycles because generally these vehicles can deliver users faster to their destination, besides that this of course saves time and compared to four-wheeled vehicles, motorbikes are certainly more cost effective, and also flexible in place. Not a few are even willing to buy a used motorbike to be able to use it again to see the functions that are still worth using. However, there are more and more criteria that eventually appear on the market, so it will take quite a long time if you have to choose a used motorbike among the various brands and the condition of the motorbike. The purpose of this study will provide an overview in making it easier for prospective used motorcycle buyers to make choices that will be decided in buying a used motorcycle by applying the AHP method, which later this method can be a reference for the seller in making it easier for customers to choose, and also customers can find out the criteria also the weight of the prospective motorcycle to be purchased. And in this study, a showroom that is able to provide information and recommendations, and can influence customers to make choices, so that customers will immediately buy the vehicle of their choice is a distinct success obtained by the owner in running a business of buying and selling used motorcycles. After knowing each alternative value for each criterion, the sub-criteria value is taken from the eigenvector value to get the result that the 3rd motor has the largest weight of 0.40 after that an interface is made based on the existing ERD design